Whole-cell system for cytochrome P450 monooxygenases biocatalysis - Hannemann, Frank; Bleif, Sabrina; Gerber, Adrian; Kleser, Michael; Bernhardt, Rita (2019)
The subject of the present invention is a whole-cell catalysis process for converting substrates of cytochrome P450 monooxygenases of eukaryotic origin into valuable biotechnological products. The subject of the present invention is also microorganisms genetically engineered to achieve those biotransformations with high rates and processes to prepare these microorganism strains.